Comparison of Ag-ELISA with conventional parasitological techniques for field diagnosis of bovine trypanosomiasis at Bedelle, Ethiopia - YESHIDINBER, TALARGIE; EGUALE, TADESSE (The Indian Journal of Animal Sciences, 2014)
The efficacy of parasitological techniques: stained blood film (BF) examination and micro haematocrit centrifugation technique (MHCT) were compared with monoclonal antibody based antigen detection enzyme linked immunosorbent assay (Ag-ELISA) in 360 indigenous zebu cattle at BedelJe area, western Ethiopia for diagnosis of trypanosomiasis. Of the 360 samples, parasitemia was detected in 24 (6.7%), 23 (6.4%) and 31 (8.6%) by BF, MHCT and by combination of both tests, respectively, while Ag-ELISA detected circulating antigen in 167 (46.4%) of the samples. Some samples positive by MHCT were negative by BF and vice versa. Ag-ELISA detected circulating trypanosome antigens in 27 (87.1 %) of31 parasite positive samples, making sensitivity of Ag-ELISA 87.1 %. The sensitivity of combined parasitological tests was 16.2%. Present results indicate that Ag-ELISA is at least 5-times more sensitive than the sensitivity of combined BF and MHCT. While parasitologicaltests detected no mixed infection, Ag-ELISA detected 73 (43.7%) or total antigenemic samples and 18 (66.7%) of the antigen and parasite positive samples to be infected by 2 or 3 species of trypanosomes, viz. Trypanosoma vlvax, T. congolense and T. brucei. Both parasitological tests and Ag-ELISA revealed T.vivax the most prevalent and T. brucei the least prevalent in the area.